Dry sliding tribological properties of A356-SiCP aluminum matrix composites prepared by vacuum stir casting. Issue 5 (28th May 2021) - Pan, Jiaqi; Liu, Xiaoshan; He, Guoqiu; Ge, Bin; Le, Peiwen; Li, Jingquan; Zhou, Zhiqiang
Abstract : Purpose: The purpose of this paper is to understand the effect of particle content, applied load and sliding speed on the tribological properties of A356-SiCP composites manufactured using a newly developed vacuum stir casting technique. Design/methodology/approach: A356 alloy reinforced with 10, 15 and 20 vol% SiC particles was prepared by vacuum stir casting. Tribological tests were carried out on block-on-ring tribometer under dry sliding conditions, room temperature. Wear mechanism was investigated by scanning electron microscope and energy dispersion spectrum. Findings: SiCP is homogeneously dispersed in the matrix. The increase in SiCP content decrease wear rate, but it leads to an increase in coefficient of friction. The wear rate increase and friction coefficient present different variation trends with increasing load. For A356-20%SiCP composite, when the load is less than 10 MPa, wear rate and friction coefficient under sliding speed of 400 rpm are lower than those of 200 rpm. Wear mechanism transition from abrasion, oxidation, delamination, adhesion to plastic flow as load and sliding speed increasing. Practical implications: Results of this study will help guide the use of A356-SiCP in many automotive products such as brake rotors, brake pads, brake drums and pistons. Originality/value: There are few paper studies the effect of particle content, applied load and sliding speed on the tribological properties of A356-SiCP composites. Aluminum matrix composites with uniform distribution of reinforcing particles were successfully prepared by using the newly developed vacuum stir casting technique.